Pengaruh Minat Belajar dan Pemberian Tugas terhadap Prestasi Belajar Mata Pelajaran Fiqih - Rudy Subyantoro (Program Pascasarjana UNU Surakarta, 2022)
This study aims to determine the effect of interest in learning on learning achievement in fiqh subjects, giving assignments on learning achievement in Fiqh subjects, and the influence of interest in learning and assignment to learning achievement in Fiqh subjects. This research is quantitative. The population in this study were students in grades 7 and 8 of MTs Negeri 3 Sukoharjo for the 2020/2021 academic year, totaling 239 students. The sample of this study was 150 students of MTs Negeri 3 Sukoharjo for the academic year 2020/2021 with the sampling technique of proportionate stratified random sampling. Data collection techniques using a questionnaire (questionnaire) and documentation. Testing the instrument using validity and reliability tests. Classical assumption test using normality test and linearity test. The data analysis technique used Multiple Linear Regression, F test, t-test, and coefficient of determination (R2). The results showed that the influence of interest in learning on the learning achievement of students in fiqh subjects at MTs Negeri 3 Sukoharjo for the 2020/2021 academic year proved to have a significantly positive effect. Giving assignments in Fiqh subjects to Fiqh Learning Achievements has been proven to have a significantly positive impact. The influence of learning interest and Fiqh subject assignments at MTs Negeri 3 Sukoharjo for the 2020/2021 academic year together has a significant effect.